Habitat use and ranging behaviour of GPS tracked juvenile golden eagles (Aquila chrysaetos) - Sandgren, Carolin (2012)
Throughout its wide distribution in the northern hemisphere, the golden eagle occurs in a diverse range of environments, e.g., mountainous, forest and open areas. The literature on juvenile golden eagles is limited, and this study provides further knowledge on habitat use and ranging behaviour during the post-fledging period in boreal Sweden. A total of 14 golden eagle juveniles were tagged with GPS transmitters during 2010 and 2011, and nine could be followed during the entire post-fledging period from fledging until migration. The juveniles fledged at the end of July and beginning of August and initiated migration during October and beginning of November. The length of the post-fledging period, until migration started, ranged from 49 to 97 days. During this period, the juveniles’ distance from their natal nest and their GPS height increased with time as their flying abilities developed. The juveniles showed a preference for clearcuts and edges between clearcuts and forest, probably because these habitats had prominent properties as hunting grounds due to prey availability, openness and occurrence of look-out posts. The juveniles also preferred lichen-pine forest, which was most likely used for roosting. Furthermore, the juveniles showed a preference for south-facing slopes, where they could take advantage of thermal updrafts for flying. The results show that a landscape mosaic of open areas and older pine forest could be favourable for the juvenile eagles and that south-facing slopes should be excluded from forestry and wind farm establishment. Dense, younger forest within wind farms could possibly discourage the juvenile eagles from the wind farm.